Campanian-Eocene dinoflagellate cyst biostratigraphy in the Southern Andean foreland basin: Implications for Drake Passage throughflow - Bijl, Peter (2021)
Fil: Bijl, Peter. Department of Earth Sciences, Laboratory of Palaeobotany and Palynology, Utrecht University. The Netherlands.